Predictors of all‐cause mortality and ischemic events within and beyond 1 year after an acute coronary syndrome: Results from the EPICOR registry - Rossello, Xavier (Clin Cardiol, 2018)
BACKGROUND: Patients discharged after an acute coronary syndrome (ACS) have substantial risk of recurrent ischemic events or dying. HYPOTHESIS: A difference may exist in risk predictors for all‐cause mortality and ischemic events between year 1 and 2 of follow‐up post‐ACS. METHODS: EPICOR (NCT01171404) was a prospective, international, real‐world cohort study of consecutive patients hospitalized for ACS within 24 hours of symptom onset and surviving to discharge. Total of 10 568 patients were enrolled (555 hospitals; 20 countries) and followed‐up for 2 years. From these, 4943 were admitted with ST‐elevation myocardial infarction (STEMI) and 5625 with non‐ST‐elevation ACS (NSTE‐ACS). Potential baseline predictors of major adverse cardiac and cerebrovascular events (MACCE; death, non‐fatal myocardial infarction [MI], non‐fatal stroke) were evaluated in year 1 and 2 post‐discharge. RESULTS: MACCE incidence per 100 person‐years at risk within and after 1 year was 5.3 vs 3.6, primarily death (4.1 vs 2.3), with no significant differences for MI or stroke. Older age, lack of coronary revascularization, raised creatinine, low hemoglobin, previous cardiac disease, previous chronic obstructive pulmonary disease, raised glucose, male sex, and geographic region were risk factors for MACCE in both year 1 and 2. By contrast, low ejection fraction, poorer quality of life, low body mass index (BMI) <20 kg/m(2), in‐hospital cardiac complications, and Killip class lost predictive power after 1 year. CONCLUSION: We observed continuous MACCE risk during 2 years of follow‐up after discharge for ACS, with greater mortality within the first year. Specific predictors at discharge for events after 1 year could not be identified.